A co-enquiry journey into early childhood settings: a rapid appraisal approach for the joint construction of knowledge - Buckley, Amma; Giamminuti, Stefania; Merewether, Jane; Tye, Marian; Kuzich, Sonja (Routledge, 2018)
This chapter outlines a co-enquiry journey involving academic researchers and public sector funders in the joint construction of knowledge about early childhood in regional Western Australian settings. The focal approach for the South West Early Childhood Project (SWECP) involved ‘rapid appraisal’ while largely utilising qualitative research methods such as interviews and focus groups; the enquiry was augmented by background profiling, photography and field visits. In providing a process analysis, the chapter outlines approaches that the multi-disciplinary team adopted to emerge with a shared coherent voice as they engaged with both the possibilities as well as the uncertainties of an expedited approach. While the denotation of ‘rapid’ distinguishes the approach from in-depth extended ethnographic community studies, this does not, however, imply haste in design or lack of rigour in analysis. Instead, the study involved considerable co-ordination of the research team, including formal meetings and many other informal opportunities to build trust, develop shared understandings, discuss background information, construct a common language and refine skills such as interview strategies, photography and content/context analysis. This co-partnering fostered a significant learning environment for the research team and provided policy makers with an experiential lens to translate findings into policy and strategy.